2022
DOI: 10.3390/ijerph192013094
|View full text |Cite
|
Sign up to set email alerts
|

Coping and Resilience Strategies among Ukraine War Refugees

Abstract: (1) Background: The war in Ukraine has triggered a huge humanitarian crisis: millions of refugees have escaped from their homes looking for shelter beyond Ukraine’s borders. This emergency offers a unique opportunity to investigate and to document those characteristics of the human condition that emerge in exceptional circumstances provoked by war. Based on considerations derived from recent studies on resilience, the research at the base of this paper was conducted to better understand the circumstances, stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 24 publications
2
28
0
1
Order By: Relevance
“…The influx of refugees from Ukraine to Poland caused a huge mobilization of Polish society and confirmed the durability and scale of the Polish tradition of solidarity, hospitality, and religiosity (Oviedo et al, 2022 ). Just a dozen hours after the Russian invasion of Ukraine, the first volunteers appeared at eight road border crossings (Dorohusk–Jagodzin, Zosin–Uściług, Dołhobyczów–Uhrynów, Hrebenne–Rawa Ruska, Budomierz–Hrushev, Korczowa–Krakowiec, Medyka–Szeginie and Krościenko–Smolnica; Straż Graniczna, 2022 , October 31), and at the Przemyśl railroad station (Przemyśl–Mościska railroad border crossing) ready to help Ukrainians fleeing their homeland from the effects of war.…”
Section: Resultsmentioning
confidence: 84%
See 2 more Smart Citations
“…The influx of refugees from Ukraine to Poland caused a huge mobilization of Polish society and confirmed the durability and scale of the Polish tradition of solidarity, hospitality, and religiosity (Oviedo et al, 2022 ). Just a dozen hours after the Russian invasion of Ukraine, the first volunteers appeared at eight road border crossings (Dorohusk–Jagodzin, Zosin–Uściług, Dołhobyczów–Uhrynów, Hrebenne–Rawa Ruska, Budomierz–Hrushev, Korczowa–Krakowiec, Medyka–Szeginie and Krościenko–Smolnica; Straż Graniczna, 2022 , October 31), and at the Przemyśl railroad station (Przemyśl–Mościska railroad border crossing) ready to help Ukrainians fleeing their homeland from the effects of war.…”
Section: Resultsmentioning
confidence: 84%
“…Professional psychological and therapeutic care for war refugees from Ukraine is urgent (Bouchard et al, 2022 ). It is also important to take care of refugees’ social networks and their support in religious life through chaplains and pastoral assistance and religious services in accordance with their religion (Oviedo et al, 2022 ). Religious congregations, clergy, Caritas Poland and numerous Church institutions of the Catholic Church are meeting these challenges and responding with concrete assistance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…What is also surprising is that praying has no protective effect in the case of the researched group. The positive impact of prayer was observed in the study carried out among Syrian (Kheirallah et al, 2022) and Ukrainian refugees (Oviedo et al, 2022). Spirituality has a crucial role in coping with war trauma.…”
Section: Discussionmentioning
confidence: 85%
“…Most of them are capable of coping with stress by communicating with their hosts in neighbouring countries, networking, and maintaining phone connection with their family members left in Ukraine. 16 A recent survey of 352 refugees in Przemysl, Poland demonstrated that 15–26% of them presented with severe and very severe anger, anxiety, depression, and sleep disturbance. 17 Most psychological symptoms were associated with hardships of relocation and separation from their family and loved ones left in Ukraine.…”
Section: Psychological Distress In Adultsmentioning
confidence: 99%